2021
DOI: 10.1093/jac/dkab116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic features of the poxtA linezolid resistance gene in human enterococci from France

Abstract: Objectives To describe the prevalence of poxtA among clinical linezolid-resistant enterococci (LRE) collected in France from 2016 to 2020 and to extensively characterize its genetic supports and environments. Methods All LRE clinical isolates received at the National Reference Centre for Enterococci from French hospitals between 2016 and 2020 were included. LRE isolates were screened for linezolid resistance genes (cfr-like, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The prevalence of the poxtA gene has been investigated in enterococci from food-producing animal farms in China, Italy, and Korea, as well as in linezolid-resistant Enterococcus spp. (LRE) from patients in Ireland, Spain, and France ( 13 , 16 22 ). In China, Lei et al reported that the poxtA gene was present in 5.5% (19/345) of enterococci isolated from 36 food-producing animal farms across 12 provinces in 2017 ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of the poxtA gene has been investigated in enterococci from food-producing animal farms in China, Italy, and Korea, as well as in linezolid-resistant Enterococcus spp. (LRE) from patients in Ireland, Spain, and France ( 13 , 16 22 ). In China, Lei et al reported that the poxtA gene was present in 5.5% (19/345) of enterococci isolated from 36 food-producing animal farms across 12 provinces in 2017 ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, clinical LRE isolates from different hospitals were submitted to the Spanish Reference Laboratory from 2015 to 2018, and 6.2% of them (6/97) were poxtA -positive ( 21 ). In France, out of 466 LRE received by the National Reference Centre for Enterococci from French hospitals between 2016 and 2020, 47 (10.1%) were poxtA -positive ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IS1216E-PoxtA-IS1216E segment in our study is similar to S. aureus AOUC-0915, and clinical E. faecium from Italy, Spain, indicating that the genetic background of poxtA is relatively single. 8,16,41 In addition to the conjugative plasmid pE035 detected in China, Enterococcus harboring both the optrA and poxtA genes were also found in the environment and human samples from Pakistan, Ireland, Spain, France 17,[42][43][44][45] Unexpectedly, there does not seem to be any obvious synergistic effect when optrA and poxtA coexist. Because the MIC of EFM_7150 is not only similar to optrA or poxtA alone isolates in our study but also to E. faecium C10004 isolated from Spain (8mg/L).…”
Section: Discussionmentioning
confidence: 97%
“…For example, linezolid resistant human strains of Enterococcus spp. may carry plasmids with co-resistance genes to florfenicol [5]. The cfr gene (named for chloramphenicol and florfenicol resistance) also mediates resistance to both linezolid and florfenicol in methicillin-resistant staphylococci [6].…”
Section: Introductionmentioning
confidence: 99%